Mn(II), Co(III), Ni(II), Cd(II) and Cu(II) Complexes of 2‐Thenoyltrifluoroacetone: Syntheses, Structures, Photoluminescence, Thermal, Electrochemical and Antitumor Studies on Dalton's Lymphoma Cells. Issue 32 (13th November 2017) - Nath, Paras; Bharty, Manoj K.; Dani, Rajeev K.; Tomar, Munendra S.; Acharya, Arbind
Abstract: Five complexes [Mn(ttfa)2 (py)2 ] (1 ), [Co(ttfa)3 ] (2 ), [Ni(ttfa)2 (en)] (3 ), [Cd(ttfa)2 (bpy)] (4 ), and [Cu(ttfa)2 (py)] (5 ) {where Httfa=2‐thenoyltrifluoroacetone} have been synthesized and characterized by elemental analyses, IR, UV‐Vis and single crystal X‐ray diffraction data. Both oxygen atoms of ttfa chelate with the metal ions forming six‐membered C3 O2 M chelate rings in the complexes. In complexes 1–4 the metal ion adopts a distorted octahedral geometry while the complex 5 is distorted square pyramidal. In the solid state, complexes are stabilized by various types of inter‐intramolecular interactions. Upon excitation at about 29500 cm −1, complexes 1, 2, 3 and 5 exhibit blue emissions while the complex 4 emits violet colour. Electrochemical studies of Httfa and complexes show irreversible redox behavior. Thermal degradation of the complexes as analyzed by TG‐DTA suggests the formation of their respective metal oxides as final thermally stable chemical entities. Httfa, complex 1 and 5 are studied for cytotoxicity on Dalton's lymphoma cells using MTT assay, apoptotic analysis and DNA fragmentation assay which reveals their order of activity as complex 5 > complex 1 > Httfa. Abstract : Crystal structures of Mn(II), Co(III), Ni(II), Cd(II) and Cu(II), 2‐thenoyltrifluoroacetonato complexes with N donor secondary ligand have been obtained from single crystal X‐ray diffraction data. Complexes are fluorescent and show irreversible redox behavior. Complex 1, 5 and ligand (Httfa) have been studied for antitumor activity on DL cell line and the order of their activity with their IC50 values is complex 5 > complex 1 > Httfa.